Moisture-absorbing and quick-drying polyester fiber for sportswear and method for manufacturing the same
Patent Information
- Application Number
- CN202611469494.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]与天然纤维和部分化学纤维相比,聚酯纤维亲水性较差,导致吸湿、透气能力不足,在穿着过程中易产生闷热感,降低了服装的舒适性,另外由于聚酯纤维及其织物的多孔结构使微生物易于附着,导致致病菌的传播,还会使纤维及其织物脆化变质影响使用性能,且细菌会在人体汗液等营养条件下迅速生长繁殖,对人体健康安全产生了危害
本发明利用溶胶-凝胶法制备了铜掺杂纳米氧化锌,然后以正硅酸四乙酯为硅源,氨水为催化剂,十六烷基三甲基溴化铵为阳离子表面活性剂控制二氧化硅的成核过程并在煅烧过程中脱除,从而将铜掺杂纳米氧化锌与二氧化硅进行复合制备得到纳米复合填料,其中铜离子的掺杂产生光催化活性位,扩展纳米氧化锌在可见光范围内的吸收强度,同时铜离子本身具有良好的抗菌性能,可以有效弥补光照条件不充分对纳米氧化锌抗菌活性的影响,并使二氧化硅具有多孔结构,其较高的比表面积和丰富的孔道结构具备良好的透气透湿性,有助于人体的排汗。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyester fiber technology, specifically relating to a moisture-wicking and quick-drying polyester fiber for sports fabrics and its preparation method. Background Technology
[0002] Polyester fiber is a synthetic fiber obtained by spinning polyester, which is formed by the condensation polymerization of organic diacids and diols. It is also known as PET fiber. Due to its excellent modulus, strength, elasticity, shape retention and heat resistance, polyester fiber has become one of the most widely used and consumed chemical fibers, accounting for more than 50% of the total amount of textile fibers. It is often used in home furnishings, clothing, industrial textiles and other fields. It is also one of the commonly used fabrics for summer clothing, often used to make skin clothing, quick-drying clothing, T-shirts, work clothes, sportswear and so on.
[0003] Compared with natural fibers and some chemical fibers, polyester fibers have poor hydrophilicity, resulting in insufficient moisture absorption and breathability. This can easily cause a stuffy feeling during wear, reducing the comfort of clothing. In addition, the porous structure of polyester fibers and their fabrics makes it easy for microorganisms to attach, leading to the spread of pathogens. It can also cause the fibers and fabrics to become brittle and deteriorate, affecting their performance. Furthermore, bacteria can grow and multiply rapidly under the nutrient conditions of human sweat, posing a threat to human health and safety. Summary of the Invention
[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide a moisture-wicking and quick-drying polyester fiber for sports fabrics and its preparation method. By adding modified nanocomposite fillers, the fiber products are endowed with good mechanical properties, breathability and moisture permeability, antibacterial properties and washability.
[0005] The objective of this invention can be achieved through the following technical solutions: A moisture-wicking and quick-drying polyester fiber for sports fabrics is prepared by mixing pretreated polyester chips and modified nanocomposite fillers to form polyester masterbatch, which is then produced by melt spinning. The modified nanocomposite filler is prepared by dehydration condensation reaction of 3-mercaptopropyltrimethoxysilane with nanocomposite filler to prepare thiolized nanocomposite filler, and then by grafting double bond antibacterial additives onto the surface of thiolized nanocomposite filler through thiol-alkene click reaction. The nanocomposite filler was prepared by using the sol-gel method to prepare copper-doped nano zinc oxide, and then using tetraethyl orthosilicate as silicon source, ammonia as catalyst, and hexadecyltrimethylammonium bromide as cationic surfactant to control the nucleation process of silicon dioxide and remove it during calcination, thereby combining copper-doped nano zinc oxide with silicon dioxide. The double-bonded antibacterial additive is prepared by amidation of 7-methyl acyl chloride coumarin with 3-amino-1,2,4-triazole, followed by nucleophilic substitution of the resulting nitrogen-containing heterocyclic coumarin intermediate with 3-bromo-1-propene, and then coordination of the resulting double-bonded nitrogen-containing heterocyclic coumarin derivative with silver trifluoroacetate.
[0006] Preferably, the mass ratio of the pretreated polyester chips to the modified nanocomposite filler is 1:0.005~0.02.
[0007] Preferably, the preparation method of the modified nanocomposite filler includes the following steps: A. Take anhydrous ethanol, deionized water and 3-mercaptopropyltrimethoxysilane and stir to mix. Add glacial acetic acid to adjust the pH to 4-5. Let stand for hydrolysis for 2 hours to obtain silane hydrolysate. Take the nanocomposite filler and ultrasonically disperse it in anhydrous ethanol. Then slowly add the silane hydrolysate and stir at 45-60℃ for 6-8 hours. After the reaction is completed, filter, wash and dry to prepare mercapto-modified nanocomposite filler. B. The thiolized nanocomposite filler was ultrasonically dispersed in dichloromethane to obtain a dispersion. The photoinitiator benzoin dimethyl ether was dissolved in dichloromethane. Then, the double-bonded antibacterial additive was added and stirred and mixed, and then slowly added to the dispersion. After mixing evenly, the mixture was transferred to a quartz flask and irradiated under a UV light source. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the modified nanocomposite filler.
[0008] Preferably, the preparation method of the nanocomposite filler includes the following steps: A1. Place zinc nitrate hexahydrate and copper nitrate pentahydrate in a reactor, add deionized water and stir magnetically until the solution is clear and transparent. Then add a mixed solution of citric acid and deionized water and stir to mix. Then slowly add ammonia water with a mass fraction of 25~28% to adjust the pH of the system to 8~9 and then evaporate to dryness at 80℃ to form a wet gel. A2. The wet gel was placed in a vacuum oven and dried at 100°C for 24 hours. Then the dried gel was transferred to a crucible and placed in a muffle furnace and calcined at 600°C for 3 hours in an air atmosphere. After natural cooling, copper-doped nano zinc oxide was prepared. A3. Place hexadecyltrimethylammonium bromide in a reactor, add deionized water and stir magnetically until completely dissolved. Then, slowly add ammonia water with a mass fraction of 25-28% to adjust the pH of the system to 11.5-12. Subsequently, add copper-doped nano zinc oxide and stir thoroughly for 2 hours. Then, add tetraethyl orthosilicate dropwise through a constant pressure burette and continue stirring for 4 hours. After stirring, filter, wash, and dry the product. Place the solid product in a muffle furnace and calcine at 550°C for 6 hours in an air atmosphere to prepare the nanocomposite filler.
[0009] Preferably, the molar ratio of zinc nitrate hexahydrate, copper nitrate pentahydrate, and citric acid is 1:0.05:1.3.
[0010] Preferably, the molar ratio of Zn / Si in the nanocomposite filler is 1:2.5~5.
[0011] Preferably, the preparation method of the double-bond antibacterial additive includes the following steps: B1. 7-Hydroxycoumarin was added to acetone and stirred thoroughly to dissolve. Oxaloyl chloride was added under nitrogen protection in an ice-water bath at 0°C to carry out a homogeneous reaction. After reacting for 3 hours, the product was added to dry triethylamine in 3 portions and stirred for 5 hours to remove excess oxalyl chloride and the generated hydrogen chloride. The triethylamine and byproducts were removed by filtration. The solvent was removed by vacuum distillation. Sodium hydroxide solution was added and filtered. The product was washed with deionized water and ethanol until neutral and then recrystallized with acetone to prepare 7-methyl ester acyl chloride coumarin. B2. Under ice-water bath conditions, 3-amino-1,2,4-triazole and triethylamine were added to dichloromethane, and then a mixed solution of 7-methyl ester chlorocoumarin and dichloromethane was added dropwise. After 3 hours, the ice-water bath was removed, and the mixture was then placed at 25°C for 5 hours. After the reaction was completed, the solid product obtained by rotary evaporation was washed successively with saturated sodium bicarbonate solution, a mixed solution of petroleum ether and ethyl acetate, and deionized water, and then dried under vacuum at 60°C to prepare a nitrogen-containing heterocyclic coumarin intermediate. B3. Take the nitrogen-containing heterocyclic coumarin intermediate and anhydrous potassium carbonate in a reactor, add N,N-dimethylformamide, purge with nitrogen for protection, stir and mix thoroughly at room temperature, then slowly add 3-bromo-1-propene. After the addition is complete, heat to 70℃ and stir for 3 hours. After the reaction is complete, add deionized water to quench, extract with ethyl acetate, combine the organic phases, dry with anhydrous magnesium sulfate, filter and remove the solvent by rotary evaporation, and purify by chromatographic column to prepare the double-bonded nitrogen-containing heterocyclic coumarin derivative. B4. Add the nitrogen-containing heterocyclic coumarin derivative with double bond group to anhydrous ethanol, heat to 50°C, add a mixed solution of silver trifluoroacetate and anhydrous ethanol, reflux at 70°C for 18 hours, cool to room temperature after the reaction is complete, wash the solid product obtained by rotary evaporation with a mixed solution of petroleum ether and ethyl acetate and deionized water, and dry under vacuum at 60°C to prepare the double bond group antibacterial additive.
[0012] Preferably, the molar ratio of 3-amino-1,2,4-triazole and 7-methyl acyl chloride coumarin is 1:1; and the molar ratio of the nitrogen-containing heterocyclic coumarin intermediate and 3-bromo-1-propene is 1:1.5.
[0013] Preferably, the molar ratio of the double-bonded nitrogen-containing heterocyclic coumarin derivative and silver trifluoroacetate is 1:2.
[0014] The method for preparing moisture-wicking and quick-drying polyester fibers for sports fabrics as described above includes the following steps: S1. The polyester chips are dried to remove the free water on the surface of the polyester chips and pre-crystallized. Then, the drying is continued to remove the bound water inside the polyester chips to obtain pre-treated polyester chips. S2. Pretreated polyester chips and modified nanocomposite fillers are mixed, melt-blended and granulated using a twin-screw extruder, then spun using a melt spinning machine, and wound by a winding machine to obtain moisture-wicking and quick-drying polyester fibers for sports fabrics.
[0015] The beneficial effects of this invention are: This invention utilizes the sol-gel method to prepare copper-doped nano-zinc oxide. Then, using tetraethyl orthosilicate as the silicon source, ammonia as the catalyst, and hexadecyltrimethylammonium bromide as the cationic surfactant, the nucleation process of silica is controlled and removed during calcination. This allows for the composite preparation of copper-doped nano-zinc oxide and silica to obtain a nanocomposite filler. The doping of copper ions generates photocatalytic active sites, expanding the absorption intensity of nano-zinc oxide in the visible light range. Simultaneously, copper ions themselves possess excellent antibacterial properties, effectively compensating for the impact of insufficient light conditions on the antibacterial activity of nano-zinc oxide. Furthermore, the invention endows silica with a porous structure; its high specific surface area and abundant pore structure provide excellent air and moisture permeability, facilitating perspiration.
[0016] This invention prepares a nitrogen-containing heterocyclic coumarin intermediate by grafting 7-methyl ester chlorocoumarin onto a 3-amino-1,2,4-triazole molecule via an amidation reaction. Then, a nucleophilic substitution reaction is carried out between 3-bromo-1-propene and the -NH group on the nitrogen-containing heterocycle in the intermediate to prepare a double-bonded nitrogen-containing heterocyclic coumarin derivative. Subsequently, the nitrogen atom on the nitrogen-containing heterocycle in the double-bonded nitrogen-containing heterocyclic coumarin derivative is coordinated with silver trifluoroacetate, which helps to control the release rate of silver ions and achieve long-lasting antibacterial effect, thereby preparing a double-bonded antibacterial additive.
[0017] The coumarin structure in the double-bonded antibacterial additive prepared in this invention can synergistically enhance the antibacterial effect with silver ions. In addition, thiolized nanocomposite fillers are prepared by dehydration condensation reaction of 3-mercaptopropyltrimethoxysilane with nanocomposite fillers. Then, the double-bonded antibacterial additive is grafted onto the surface of the thiolized nanocomposite filler through a thiol-alkene click reaction to prepare modified nanocomposite fillers. This promotes the relatively uniform dispersion of nanocomposite fillers in the matrix material, thereby improving the mechanical properties to a certain extent. Furthermore, the double-bonded antibacterial additive is firmly bonded to the surface of the nanocomposite filler through a chemical reaction, avoiding the problem of antibacterial component migration and precipitation. Detailed Implementation
[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1: A method for preparing a nanocomposite filler includes the following steps: A1. Take 1 mol of zinc nitrate hexahydrate and 0.05 mol of copper nitrate pentahydrate and place them in a reactor. Add 200 mL of deionized water and stir magnetically until the solution is clear and transparent. Then add a mixed solution of 1.3 mol of citric acid and 20 mL of deionized water and stir to mix. Then slowly add 25% ammonia water to adjust the pH of the system to 8.5 and evaporate to dryness at 80℃ to form a wet gel. A2. The wet gel was placed in a vacuum oven and dried at 100°C for 24 hours. Then the dried gel was transferred to a crucible and placed in a muffle furnace and calcined at 600°C for 3 hours in an air atmosphere. After natural cooling, copper-doped nano zinc oxide was prepared. A3. Take 0.42 mol of cetyltrimethylammonium bromide and place it in a reactor. Add deionized water and stir magnetically until completely dissolved. Then, slowly add 25% ammonia water to adjust the pH of the system to 11.7. Then, add the obtained copper-doped nano zinc oxide and stir thoroughly for 2 hours. According to the Zn / Si molar ratio of 1:3.5, add tetraethyl orthosilicate dropwise through a constant pressure burette and continue stirring for 4 hours. After stirring, filter, wash and dry the solid product. Place the solid product in a muffle furnace and calcine at 550°C for 6 hours in an air atmosphere to prepare the nanocomposite filler.
[0020] Example 2: A method for preparing a double-bond antibacterial additive includes the following steps: B1. Take 5g of 7-hydroxycoumarin and add it to 100mL of acetone. Stir and dissolve thoroughly. Add 5g of oxaloyl chloride under nitrogen protection in an ice-water bath at 0℃ for homogeneous reaction. After reacting for 3h, add the product to 6g of dry triethylamine in 3 portions and stir for 5h to remove excess oxaloyl chloride and generated hydrogen chloride. Filter to remove triethylamine and byproducts. Remove solvent by vacuum distillation. Add 1% sodium hydroxide solution and filter. Wash with deionized water and ethanol until neutral and recrystallize with acetone to prepare 7-methyl ester acyl chloride coumarin. B2. Under ice-water bath conditions, 0.84 g of 3-amino-1,2,4-triazole and 1.52 g of triethylamine were added to 100 mL of dichloromethane, and then a mixed solution of 2.52 g of 7-methyl ester chlorocoumarin and 40 mL of dichloromethane was added dropwise. After 3 h, the ice-water bath was removed, and the mixture was then placed at 25 °C for 5 h. After the reaction was completed, the solid product obtained by rotary evaporation was washed successively with saturated sodium bicarbonate solution, a mixed solution of petroleum ether and ethyl acetate in a volume ratio of 5:1, and deionized water, and then dried under vacuum at 60 °C to prepare a nitrogen-containing heterocyclic coumarin intermediate. B3. Take 3.01 g of nitrogen-containing heterocyclic coumarin intermediate and 2.07 g of anhydrous potassium carbonate and place them in a reactor. Add 50 mL of N,N-dimethylformamide, purge with nitrogen for protection, and stir thoroughly at room temperature. Then slowly add 1.82 g of 3-bromo-1-propene. After the addition is complete, raise the temperature to 70 °C and stir for 3 h. After the reaction is complete, add deionized water to quench the reaction, extract with ethyl acetate, combine the organic phases, dry with anhydrous magnesium sulfate, filter, remove the solvent by rotary evaporation, and purify by chromatographic column to prepare the double-bonded nitrogen-containing heterocyclic coumarin derivative. B4. Take 0.85g of the double-bonded nitrogen-containing heterocyclic coumarin derivative and add it to 50mL of anhydrous ethanol. Heat to 50℃, add a mixed solution of 1.1g of silver trifluoroacetate and 20mL of anhydrous ethanol, and reflux at 70℃ for 18h. After the reaction is complete, cool to room temperature. The solid product obtained by rotary evaporation is washed successively with a mixed solution of petroleum ether and ethyl acetate in a volume ratio of 1:2 and deionized water, and dried under vacuum at 60℃ to prepare the double-bonded antibacterial additive.
[0021] Example 3: A method for preparing a modified nanocomposite filler includes the following steps: A. Take 8 mL of anhydrous ethanol, 2 mL of deionized water and 3.2 mL of 3-mercaptopropyltrimethoxysilane and stir to mix. Add glacial acetic acid to adjust the pH to 4. Let stand for 2 h to hydrolyze and obtain silane hydrolysate. Take 2 g of the nanocomposite filler prepared in Example 1 and ultrasonically disperse it in 100 mL of anhydrous ethanol. Then slowly add silane hydrolysate and stir at 50 °C for 8 h. After the reaction is completed, filter, wash and dry to prepare mercapto-modified nanocomposite filler. B. Take 2g of thiolized nanocomposite filler and ultrasonically disperse it in 100mL of dichloromethane to obtain a dispersion. Take 0.02g of photoinitiator benzoin dimethyl ether and dissolve it in 20mL of dichloromethane. Then add 1.12g of the double bond antibacterial additive prepared in Example 2, stir and mix, and slowly add it to the dispersion. After mixing evenly, transfer it to a quartz flask and irradiate it under a UV light source. After the reaction is completed, filter, wash and dry to obtain the modified nanocomposite filler.
[0022] Example 4: A method for preparing moisture-wicking and quick-drying polyester fiber for sports fabrics, comprising the following steps: S1. Place the polyester chips in an 80°C forced-air oven and dry for 1 hour. Then raise the temperature to 95°C and continue drying for 2 hours to remove the free water on the surface of the polyester chips and perform pre-crystallization. Then place them in a 100°C vacuum oven and dry for 1 hour. Then raise the temperature to 120°C and dry for 24 hours to remove the bound water inside the polyester chips and obtain pretreated polyester chips. S2. The pretreated polyester chips and the modified nanocomposite filler prepared in Example 3 were mixed at a mass ratio of 1:0.007. The mixture was melt-blended and granulated using a twin-screw extruder, and then spun using a melt spinning machine. The temperature of each zone of the screw was 290~300℃, the temperature of the bend and the box was 295℃, the spinneret had 36 holes, the winding speed was 500~1000m / min, and the yarn was stretched 3 times at 80~100℃ to prepare moisture-wicking and quick-drying polyester fibers for sports fabrics.
[0023] Example 5: A method for preparing moisture-wicking and quick-drying polyester fiber for sports fabrics, comprising the following steps: S1. Place the polyester chips in an 80°C forced-air oven and dry for 1 hour. Then raise the temperature to 95°C and continue drying for 2 hours to remove the free water on the surface of the polyester chips and perform pre-crystallization. Then place them in a 100°C vacuum oven and dry for 1 hour. Then raise the temperature to 120°C and dry for 24 hours to remove the bound water inside the polyester chips and obtain pretreated polyester chips. S2. The pretreated polyester chips and the modified nanocomposite filler prepared in Example 3 were mixed at a mass ratio of 1:0.014. The mixture was melt-blended and granulated using a twin-screw extruder, and then spun using a melt spinning machine. The temperature of each zone of the screw was 290~300℃, the temperature of the bend and the box was 295℃, the spinneret had 36 holes, the winding speed was 500~1000m / min, and the yarn was stretched 3 times at 80~100℃ to prepare moisture-wicking and quick-drying polyester fibers for sports fabrics.
[0024] Example 6: A method for preparing moisture-wicking and quick-drying polyester fibers for sports fabrics, comprising the following steps: S1. Place the polyester chips in an 80°C forced-air oven and dry for 1 hour. Then raise the temperature to 95°C and continue drying for 2 hours to remove the free water on the surface of the polyester chips and perform pre-crystallization. Then place them in a 100°C vacuum oven and dry for 1 hour. Then raise the temperature to 120°C and dry for 24 hours to remove the bound water inside the polyester chips and obtain pretreated polyester chips. S2. The pretreated polyester chips and the modified nanocomposite filler prepared in Example 3 were mixed at a mass ratio of 1:0.018. The mixture was melt-blended and granulated using a twin-screw extruder, and then spun using a melt spinning machine. The temperature of each zone of the screw was 290~300℃, the temperature of the bend and the box was 295℃, the spinneret had 36 holes, the winding speed was 500~1000m / min, and the yarn was stretched 3 times at 80~100℃ to prepare moisture-wicking and quick-drying polyester fibers for sports fabrics.
[0025] Comparative Example 1: A method for preparing modified copper-doped nano-zinc oxide includes the following steps: A. Take 8 mL of anhydrous ethanol, 2 mL of deionized water and 3.2 mL of 3-mercaptopropyltrimethoxysilane and stir to mix. Add glacial acetic acid to adjust the pH to 4 and let stand for hydrolysis for 2 h to obtain silane hydrolysate. Take 2 g of copper-doped nano zinc oxide prepared in Example 1 and ultrasonically disperse it in 100 mL of anhydrous ethanol. Then slowly add silane hydrolysate and stir at 50 °C for 8 h. After the reaction is completed, filter, wash and dry to prepare mercapto-copper-doped nano zinc oxide. B. Take 2g of thiolized copper-doped nano zinc oxide and ultrasonically disperse it in 100mL of dichloromethane to obtain a dispersion. Take 0.02g of photoinitiator benzoin dimethyl ether and dissolve it in 20mL of dichloromethane. Then add 1.12g of the double-bonded antibacterial additive prepared in Example 2, stir and mix, and slowly add it to the dispersion. After mixing evenly, transfer it to a quartz flask and irradiate it under a UV light source. After the reaction is completed, filter, wash and dry to obtain modified copper-doped nano zinc oxide.
[0026] Comparative Example 2: A method for preparing a modified nanocomposite filler includes the following steps: A. Take 8 mL of anhydrous ethanol, 2 mL of deionized water and 3.2 mL of 3-mercaptopropyltrimethoxysilane and stir to mix. Add glacial acetic acid to adjust the pH to 4. Let stand for 2 h to hydrolyze and obtain silane hydrolysate. Take 2 g of the nanocomposite filler prepared in Example 1 and ultrasonically disperse it in 100 mL of anhydrous ethanol. Then slowly add silane hydrolysate and stir at 50 °C for 8 h. After the reaction is completed, filter, wash and dry to prepare mercapto-modified nanocomposite filler. B. Take 2g of thiolized nanocomposite filler and ultrasonically disperse it in 100mL of dichloromethane to obtain a dispersion. Take 0.02g of photoinitiator benzoin dimethyl ether and dissolve it in 20mL of dichloromethane. Then add 1.12g of the double-bonded nitrogen-containing heterocyclic coumarin derivative prepared in Example 2, stir and mix, and slowly add it to the dispersion. After mixing evenly, transfer it to a quartz flask and irradiate it under a UV light source. After the reaction is completed, filter, wash and dry to obtain the modified nanocomposite filler.
[0027] Comparative Example 3: A method for preparing moisture-wicking and quick-drying polyester fibers for sports fabrics, comprising the following steps: S1. Place the polyester chips in an 80°C forced-air oven and dry for 1 hour. Then raise the temperature to 95°C and continue drying for 2 hours to remove the free water on the surface of the polyester chips and perform pre-crystallization. Then place them in a 100°C vacuum oven and dry for 1 hour. Then raise the temperature to 120°C and dry for 24 hours to remove the bound water inside the polyester chips and obtain pretreated polyester chips. S2. Pretreated polyester chips and modified copper-doped nano zinc oxide prepared in Comparative Example 1 were mixed at a mass ratio of 1:0.018. The mixture was melt-blended and granulated using a twin-screw extruder, and then spun using a melt spinning machine. The temperature of each zone of the screw was 290~300℃, the temperature of the bend tube and the box was 295℃, the spinneret had 36 holes, the winding speed was 500~1000m / min, and the yarn was stretched 3 times at 80~100℃ to prepare moisture-wicking and quick-drying polyester fibers for sports fabrics.
[0028] Comparative Example 4: A method for preparing moisture-wicking and quick-drying polyester fibers for sports fabrics, comprising the following steps: S1. Place the polyester chips in an 80°C forced-air oven and dry for 1 hour. Then raise the temperature to 95°C and continue drying for 2 hours to remove the free water on the surface of the polyester chips and perform pre-crystallization. Then place them in a 100°C vacuum oven and dry for 1 hour. Then raise the temperature to 120°C and dry for 24 hours to remove the bound water inside the polyester chips and obtain pretreated polyester chips. S2. Pretreated polyester chips and modified nanocomposite fillers prepared in Comparative Example 2 were mixed at a mass ratio of 1:0.018. The mixture was melt-blended and granulated using a twin-screw extruder, and then spun using a melt spinning machine. The temperature of each zone of the screw was 290~300℃, the temperature of the bend tube and the box was 295℃, the spinneret had 36 holes, the winding speed was 500~1000m / min, and the yarn was stretched 3 times at 80~100℃ to prepare moisture-wicking and quick-drying polyester fibers for sports fabrics.
[0029] Comparative Example 5: A method for preparing moisture-wicking and quick-drying polyester fibers for sports fabrics, comprising the following steps: S1. Place the polyester chips in an 80°C forced-air oven and dry for 1 hour. Then raise the temperature to 95°C and continue drying for 2 hours to remove the free water on the surface of the polyester chips and perform pre-crystallization. Then place them in a 100°C vacuum oven and dry for 1 hour. Then raise the temperature to 120°C and dry for 24 hours to remove the bound water inside the polyester chips and obtain pretreated polyester chips. S2. The pretreated polyester chips and the nanocomposite filler prepared in Example 1 were mixed at a mass ratio of 1:0.018. The mixture was melt-blended and granulated using a twin-screw extruder, and then spun using a melt spinning machine. The temperature of each zone of the screw was 290~300℃, the temperature of the bend tube and the box was 295℃, the spinneret had 36 holes, the winding speed was 500~1000m / min, and the yarn was stretched 3 times at 80~100℃ to prepare moisture-wicking and quick-drying polyester fibers for sports fabrics.
[0030] Performance testing (1) The polyester fibers prepared in Examples 4-6 and Comparative Examples 3-5 were tested for tensile properties in accordance with GB / T 14337-2022. The clamping distance was set to 10 mm and the tensile speed was 10 mm / min. At least 30 monofilaments of each sample were randomly tested and the average value was taken. The antibacterial properties were tested in accordance with GB / T 20944.3-2008. The fiber washing conditions were in accordance with GB / T 20944.3-2008. The test conditions were 40℃, ECE standard detergent, liquor ratio of 1:30, and cyclic washing. Each cycle was about 30 min. After each wash, the fibers were rinsed with clean water and then dried. This was counted as one cycle. A total of 50 cycles were performed. The data results are shown in Table 1.
[0031] (2) The polyester fibers prepared in Examples 4-6 and Comparative Examples 3-5 were twisted and then woven in plain weave on a small sample loom with a warp density of 600 threads / 10cm and a weft density of 400 threads / 10cm. The air permeability and moisture permeability were tested: the air permeability test was performed using a YG461E fully automatic air permeability tester according to GB / T 5453-1997; the moisture permeability test was performed using a YG601H moisture permeability analyzer according to GB / T 12704.1-2009. The data results are shown in Table 1.
[0032] Table 1 Sample performance test results <![CDATA[Breaking strength / cN·dtex -1 > 4.44 4.62 4.87 4.66 4.85 4.06 Elongation at break / % 25.4 26.8 28.1 27.3 28.0 20.7 <![CDATA[Air permeability / mm·s -1 > 80 82 83 72 82 83 <![CDATA[Moisture vapor transmission rate / g / m 2 ·24h]]> 7123 7220 7169 6263 7184 7217 Escherichia coli inhibition rate / % 99.97 99.99 99.99 99.99 81.23 61.66 E. coli inhibition rate after water washing / % 98.36 98.57 98.74 98.72 79.20 57.18 Staphylococcus aureus inhibition rate / % 99.98 99.99 99.99 99.99 81.44 61.81 Staphylococcus aureus inhibition rate after water washing / % 98.55 98.76 98.92 98.91 79.45 57.55 As can be seen from the data in Table 1, the fiber samples prepared in Examples 4-6 of this invention possess good mechanical properties, air and moisture permeability, antibacterial properties, and washability. In Comparative Example 3, the modified copper-doped nano-zinc oxide, which did not introduce porous silica as a carrier, showed lower measured air and moisture permeability compared to Examples 4-6. This is because the introduced silica has a higher specific surface area and richer pore structure, providing good air and moisture permeability and facilitating perspiration. Similarly, in Comparative Example 4, the modified nanocomposite filler, which did not introduce silver trifluoroacetate, showed lower measured antibacterial rates against Escherichia coli and Staphylococcus aureus compared to Examples 4-6. This is because the introduction of silver trifluoroacetate allows it to coordinate with the nitrogen atoms on the nitrogen-containing heterocycles in the double-bonded nitrogen-containing heterocyclic coumarin derivative structure. In contrast, the complexation of the nanocomposite filler improved the antibacterial properties of the sample to a certain extent. In Comparative Example 5, the nanocomposite filler was not modified, and its measured tensile strength, elongation at break, antibacterial properties, and antibacterial properties after washing were lower than those in Examples 4-6. This is because modifying the nanocomposite filler is beneficial to the dispersion of the nanocomposite filler, improves the interfacial compatibility between the nanocomposite filler and the matrix material, and thus improves the mechanical properties. It also shows that using chemical reactions to bond the double-bonded antibacterial additives to the surface of the nanocomposite filler through strong chemical bonds is beneficial to further improve the antibacterial properties and water resistance of the sample.
[0033] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0034] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A moisture-wicking and quick-drying polyester fiber for sports fabrics, characterized in that, Polyester masterbatch is prepared by mixing pretreated polyester chips and modified nanocomposite fillers, and then produced by melt spinning. The modified nanocomposite filler is prepared by dehydration condensation reaction of 3-mercaptopropyltrimethoxysilane with nanocomposite filler to prepare thiolized nanocomposite filler, and then by grafting double bond antibacterial additives onto the surface of thiolized nanocomposite filler through thiol-alkene click reaction. The nanocomposite filler was prepared by using the sol-gel method to prepare copper-doped nano zinc oxide, and then using tetraethyl orthosilicate as silicon source, ammonia as catalyst, and hexadecyltrimethylammonium bromide as cationic surfactant to control the nucleation process of silicon dioxide and remove it during calcination, thereby combining copper-doped nano zinc oxide with silicon dioxide. The double-bonded antibacterial additive is prepared by amidation of 7-methyl acyl chloride coumarin with 3-amino-1,2,4-triazole, followed by nucleophilic substitution of the resulting nitrogen-containing heterocyclic coumarin intermediate with 3-bromo-1-propene, and then coordination of the resulting double-bonded nitrogen-containing heterocyclic coumarin derivative with silver trifluoroacetate.
2. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 1, characterized in that, The mass ratio of the pretreated polyester chips to the modified nanocomposite filler is 1:0.005~0.
02.
3. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 1, characterized in that, The preparation method of the modified nanocomposite filler includes the following steps: A. Take anhydrous ethanol, deionized water and 3-mercaptopropyltrimethoxysilane and stir to mix. Add glacial acetic acid to adjust the pH to 4-5. Let stand for hydrolysis for 2 hours to obtain silane hydrolysate. Take the nanocomposite filler and ultrasonically disperse it in anhydrous ethanol. Then slowly add the silane hydrolysate and stir at 45-60℃ for 6-8 hours. After the reaction is completed, filter, wash and dry to prepare mercapto-modified nanocomposite filler. B. The thiolized nanocomposite filler was ultrasonically dispersed in dichloromethane to obtain a dispersion. The photoinitiator benzoin dimethyl ether was dissolved in dichloromethane. Then, the double-bonded antibacterial additive was added and stirred and mixed, and then slowly added to the dispersion. After mixing evenly, the mixture was transferred to a quartz flask and irradiated under a UV light source. After the reaction was completed, the mixture was filtered, washed, and dried to obtain the modified nanocomposite filler.
4. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 3, characterized in that, The preparation method of the nanocomposite filler includes the following steps: A1. Place zinc nitrate hexahydrate and copper nitrate pentahydrate in a reactor, add deionized water and stir magnetically until the solution is clear and transparent. Then add a mixed solution of citric acid and deionized water and stir to mix. Then slowly add ammonia water with a mass fraction of 25~28% to adjust the pH of the system to 8~9 and then evaporate to dryness at 80℃ to form a wet gel. A2. The wet gel was placed in a vacuum oven and dried at 100°C for 24 hours. Then the dried gel was transferred to a crucible and placed in a muffle furnace and calcined at 600°C for 3 hours in an air atmosphere. After natural cooling, copper-doped nano zinc oxide was prepared. A3. Place hexadecyltrimethylammonium bromide in a reactor, add deionized water and stir magnetically until completely dissolved. Then, slowly add ammonia water with a mass fraction of 25-28% to adjust the pH of the system to 11.5-12. Subsequently, add copper-doped nano zinc oxide and stir thoroughly for 2 hours. Then, add tetraethyl orthosilicate dropwise through a constant pressure burette and continue stirring for 4 hours. After stirring, filter, wash, and dry the product. Place the solid product in a muffle furnace and calcine at 550°C for 6 hours in an air atmosphere to prepare the nanocomposite filler.
5. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 4, characterized in that, The molar ratio of zinc nitrate hexahydrate, copper nitrate pentahydrate, and citric acid is 1:0.05:1.
3.
6. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 4, characterized in that, The molar ratio of Zn / Si in the nanocomposite filler is 1:2.5~5.
7. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 1, characterized in that, The preparation method of the double bond antibacterial additive includes the following steps: B1. 7-Hydroxycoumarin was added to acetone and stirred thoroughly to dissolve. Oxaloyl chloride was added under nitrogen protection in an ice-water bath at 0°C to carry out a homogeneous reaction. After reacting for 3 hours, the product was added to dry triethylamine in 3 portions and stirred for 5 hours to remove excess oxalyl chloride and the generated hydrogen chloride. The triethylamine and byproducts were removed by filtration. The solvent was removed by vacuum distillation. Sodium hydroxide solution was added and filtered. The product was washed with deionized water and ethanol until neutral and then recrystallized with acetone to prepare 7-methyl ester acyl chloride coumarin. B2. Under ice-water bath conditions, 3-amino-1,2,4-triazole and triethylamine were added to dichloromethane, and then a mixed solution of 7-methyl ester chlorocoumarin and dichloromethane was added dropwise. After 3 hours, the ice-water bath was removed, and the mixture was then placed at 25°C for 5 hours. After the reaction was completed, the solid product obtained by rotary evaporation was washed successively with saturated sodium bicarbonate solution, a mixed solution of petroleum ether and ethyl acetate, and deionized water, and then dried under vacuum at 60°C to prepare a nitrogen-containing heterocyclic coumarin intermediate. B3. Take the nitrogen-containing heterocyclic coumarin intermediate and anhydrous potassium carbonate in a reactor, add N,N-dimethylformamide, purge with nitrogen for protection, stir and mix thoroughly at room temperature, then slowly add 3-bromo-1-propene. After the addition is complete, heat to 70℃ and stir for 3 hours. After the reaction is complete, add deionized water to quench, extract with ethyl acetate, combine the organic phases, dry with anhydrous magnesium sulfate, filter and remove the solvent by rotary evaporation, and purify by chromatographic column to prepare the double-bonded nitrogen-containing heterocyclic coumarin derivative. B4. Add the nitrogen-containing heterocyclic coumarin derivative with double bond group to anhydrous ethanol, heat to 50°C, add a mixed solution of silver trifluoroacetate and anhydrous ethanol, and reflux at 70°C for 18 hours. After the reaction is completed, cool to room temperature, and wash the solid product obtained by rotary evaporation with a mixed solution of petroleum ether and ethyl acetate and deionized water in sequence. Dry under vacuum at 60°C to prepare the double bond group antibacterial additive.
8. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 7, characterized in that, The molar ratio of 3-amino-1,2,4-triazole and 7-methyl acyl chloride coumarin is 1:1; the molar ratio of the nitrogen-containing heterocyclic coumarin intermediate and 3-bromo-1-propene is 1:1.
5.
9. The moisture-wicking and quick-drying polyester fiber for sports fabrics according to claim 7, characterized in that, The molar ratio of the double-bonded nitrogen-containing heterocyclic coumarin derivative to silver trifluoroacetate is 1:
2.
10. A method for preparing moisture-wicking and quick-drying polyester fibers for sports fabrics according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1. The polyester chips are dried to remove the free water on the surface of the polyester chips and pre-crystallized. Then, the drying is continued to remove the bound water inside the polyester chips to obtain pre-treated polyester chips. S2. Pretreated polyester chips and modified nanocomposite fillers are mixed, melt-blended and granulated using a twin-screw extruder, then spun using a melt spinning machine, and wound by a winding machine to obtain moisture-wicking and quick-drying polyester fibers for sports fabrics.